Direct molecular typing of Bordetella pertussis from clinical specimens submitted for diagnostic quantitative (real-time) PCR - Litt, David J.; Jauneikaite, Elita; Tchipeva, Draga; Harrison, Timothy G.; Fry, Norman K. (Journal of medical microbiology, 2012)
Molecular typing of Bordetella pertussis is routinely performed on bacterial isolates, but not on DNA extracted from nasopharyngeal aspirates or pernasal swabs submitted for diagnostic real-time PCR (qPCR). We investigated whether these DNA extracts were suitable for multilocus variable-number tandem repeat analysis (MLVA) and DNA sequence-based typing. We analysed all the available qPCR-positive samples received by our laboratory from patients <1 year of age between January 2008 and August 2010. Eighty-one per cent (106/131) of these generated a complete MLVA profile. This rose to 92 % (105/114) if only samples positive for both of the two targets used for the B. pertussis PCR (insertion element IS481 and pertussis toxin promoter ptxP) were analysed. Sequence-based typing of the pertactin, pertussis toxin S1 subunit and pertussis promoter regions (prn, ptxA and ptxP) was attempted on 89 of the DNA extracts that had generated a full MLVA profile. Eighty-three (93 %) of these produced complete sequences for all three targets. Comparison of molecular typing data from the 89 extracts with those from 111 contemporary bacterial isolates showed that the two sources yielded the same picture of the B. pertussis population [dominated by the MLVA-27 prn(2) ptxA(1) ptxP(3) clonal type]. There was no significant difference in MLVA type distribution or diversity between the two sample sets. This suggests that clinical extracts can be used in place of, or to complement, bacterial cultures for typing purposes (at least, in this age group). With small modifications to methodology, generating MLVA and sequence-based typing data from qPCR-positive clinical DNA extracts is likely to generate a complete dataset in the majority of samples from the <1 year age group. Its success with samples from older subjects remains to be seen. However, our data suggest that it is suitable for inclusion in molecular epidemiological studies of the B. pertussis population or as a tool in outbreak investigations.